Dendroclimatic Analysis of Scots Pine (Pinus sylvestris L.) Radial Growth in the European North-East of Russia - I. N. Kutyavin; A. V. Manov; И. Н. Кутявин; А. В. Манов (Izvestiya Rossiiskoi Akademii Nauk. Seriya Geograficheskaya, 2022)
The study’s results of the climatic signal with a radial growth of Scots pine (Pinus sylvestris L.) on automorphic and hydromorphic soils of the European North-East of Russia (Komi Republic) are presented. Wood samples (cores and cuts) were taken from seven sites located in different subzones of the taiga. Based on these samples, tree-ring chronologies of pine were built, and the relationship between growth and climatic parameters (air temperature, climatic precipitation) was revealed. According to instrumental meteorological observations, in the study area, since the beginning of the 70s of the 20th century, there has been a tendency to an increase in air temperature and the amount of precipitation. In the latitudinal and longitudinal gradients, these indicators are manifested unequally. Analysis of the relationship between climate and growth showed that the main factor providing pine growth in the northern taiga subzone and in the Northern Urals is the temperature in May, and in the middle and southern taiga subzone—in July. In the pine forests of the extremely northern taiga, a reliable negative relationship was found between the width of tree rings and precipitation in May and July. An analysis of the correlation of pine growth indices with average monthly temperatures and the precipitation amount in a floating window in the range of 25 years showed an unstable signal for the growing season. It is noted that over the past 30 years in the European Northeast, there has been a weakening of the climatic signal with wood radial growth. The correlation of the relationship between indexed pine chronologies with sliding fifteen-day values of climatic indicators showed positive relationship between radial growth and air temperature. However, this relationship became insignificant in the middle and southern taiga at the beginning of the growing season. On the contrary, these values are replaced by precipitation. But, such a feature is not manifested in the subzones of the extreme and northern taiga. Here, to a greater ...